Investigating The Teacher Perspectives in Communicative Language Teaching in EFL Classrooms - Mu'tasim Bila; Virga Putra Darma; Utami Rosalina (Tomorrow's Education Journal, 2025)
This study investigates the opinions of English teachers in Indonesian primary schools on Communicative Language Teaching (CLT). Interviews and document analysis were used to collect data from three teachers using a qualitative descriptive method. The results indicate that although teachers place a high value on communicative competence, curriculum demands, student motivation, and resource constraints frequently cause classroom practices to combine CLT with grammar-focused instruction. Despite obstacles like huge class sizes and inadequate training, teachers adapt CLT through task-based activities, group projects, scaffolding, and culturally relevant resources. The study emphasizes that in order to improve communicative language learning in EFL classes, professional development, contextual adaptability, and supportive policies are necessary.